What Can We Do? Social Workers in Trinidad Discuss Intimate Partner Violence Against Women. (December 2021) - Nathaniel, Karene-Anne
This article presents findings from research on the Caribbean island of Trinidad with male and female social workers, exploring their views of intimate partner violence against women. The premise here is that actions of helping professionals, including social workers, are partly founded on their views of social problems and clients. Three themes emerged from the conversations as contributing to violence against women: the attitudes and behaviors of victims; societal norms and attitudes; and weak interagency collaboration. A sense of futility in intervention was apparent in the conversations. There are implications for strengthening professional self-efficacy, attitude to clients, and networking.